Surface energy matching to improve the wetting behaviour of aqueous slurries with carrier tapes for the production of large YAG transparent ceramic flakes. Issue 20 (15th October 2022) - Xi, Xiaoqian; Zhang, Le; Liu, Mingyuan; Zhou, Chunming; Zhu, Lv; Cao, Yifei; Shao, Cen; Wang, Zhongying; Wei, Cong; Ren, Zihan; Wu, Xiaodong; Fei, Bin; et al.
Abstract: Aqueous tape casting exhibits unique advantages in the production of large transparent ceramic (TC) flakes. However, the high surface energy of aqueous slurries results in poor wettability with carrier tapes, thereby making it difficult to obtain high-quality green bodies. In addition, organic additives always introduce unexpected defects into TCs. In this study, the wettabilities of an aqueous solution on various carrier tapes were compared, and the rheological behaviours of a slurry were systematically investigated. The cellophane (PT) carrier with high surface energy dramatically improved the wettability of the aqueous slurry. The organic content of the optimized slurry was as low as 12.0 wt%. The dried green body was defect-free, and its tensile strength reached 8.7 MPa. The deformation degree of the TC flakes was only approximately 0.3%. The YAG flakes with dimensions of 100 mm × 100 mm × 1 mm exhibited a high transmittance of 82.8% (@400 nm). The ideas, methods, and results of this study will accelerate the application of aqueous tape casting in the field of high-tech ceramics.